The Effect of Price Reduction on Salad Bar Purchases at a Corporate Cafeteria - Kottke, Thomas E. (Centers for Disease Control and Prevention, 2013)
The objective of this study was to determine the effect of a price reduction on salad bar purchases in a corporate cafeteria. We reduced the price of salad bar purchases by 50% during March 2012 and analyzed sales data by month for February through June 2012. We also conducted an anonymous survey. Salad bar sales by weight more than tripled during the price reduction and returned to baseline afterward. Survey respondents reported that the high price of salad relative to other choices is a barrier to purchases. Policies that make the price of salads equal to other choices in cafeterias may significantly increase healthful food consumption.